2020
DOI: 10.3847/1538-4357/abc2cb
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perturbed Milky Way Disk and the Substructures of the Outer Disk

Abstract: The recent discovery of a spiral feature in the Z − V Z phase plane in the solar neighborhood implies that the galactic disk has been remarkably affected by a dwarf galaxy passing through it some hundreds of millions of years ago. Using 429,500 Large Sky Area Multi-Object Fibre Spectroscopic Telescope K giants stars, we show that the spiral feature exists not only in the solar vicinity but it also extends to about 15 kpc from the Galactic center and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 101 publications
7
50
0
Order By: Relevance
“…With the help LAMOST K giant stars and two types of simulations, Xu et al (2020) pointed out the external perturbations might influence the outer disk beyond solar neighborhood and revealed that the flaring could be explained by perturbations qualitatively, which supports our viewpoints here about the flaring. Combining young OB type Stars and old K giant stars we could infer that the sensitive time of the flaring features to the possible perturbations might from very early time in OB population to the relatively late time in K giant population.…”
Section: Possible Scenarios For the Flaringsupporting
confidence: 80%
See 1 more Smart Citation
“…With the help LAMOST K giant stars and two types of simulations, Xu et al (2020) pointed out the external perturbations might influence the outer disk beyond solar neighborhood and revealed that the flaring could be explained by perturbations qualitatively, which supports our viewpoints here about the flaring. Combining young OB type Stars and old K giant stars we could infer that the sensitive time of the flaring features to the possible perturbations might from very early time in OB population to the relatively late time in K giant population.…”
Section: Possible Scenarios For the Flaringsupporting
confidence: 80%
“…In addition to the aforementioned disturbances, Cheng et al (2019) proposed another case, that is saying, a few decades ago, the dark matter sub-halo perturbed the disk and left marks on these young stars. Similar perturbation scenarios such as warp, stream, satellites, dwarf galaxies, dark matter sub-halos are also mentioned in Wang et al (2018aWang et al ( , 2020a; Khanna et al (2019);Bland-Hawthorn et al (2019); Xu et al (2020) and reference therein.…”
Section: Possible Scenarios For the Flaringsupporting
confidence: 56%
“…In particular, the stellar-mass density at a radius of $8 kpc is significantly higher than previous estimates 135 by approximately 0.016 M 1 /pc 3 . 47 The disk flaring phenomenon was clearly revealed by LAMOST 47,136,137 (Figure 7), which was found to be a ubiquitous phenomenon for all monoage populations. Complex features in the stellar distribution throughout the outer disk revealed by LAMOST 47,138 reflect a significantly perturbated disk (Figure 7) evolution history.…”
Section: Review Llmentioning
confidence: 93%
“…In particular, simulations of a Sgr-like satellite impacting a MW-like disk that were developed to fit the pre-Gaia data were shown to contain analogous manifestation of both the local and global signatures of vertical disequilibrium with similar spatial and velocity scales (Laporte et al 2019). Other works have reinforced these local-global connections with further views of the data, tailored simulations and analytic models (Xu et al 2020;Bland-Hawthorn & Tepper-Garcia 2020;Widrow et al 2020;Bennett & Bovy 2021).…”
Section: Introductionmentioning
confidence: 92%